Implementasi Kriptografi Vigenere Cipher Menggunakan PHP - Rama Wahyu Husein ((JurTI) Jurnal Teknologi Informasi, 2022)
Abstract– Information security in applications is very important, applications need security systems, because in some companies or even in countries information security is required, and important information that should not be accessed by random recipients of messages must be protected. To protect this information, an algorithm is needed that can cover important messages so that they cannot be read by parties who are not entitled to receive the information. Cryptography is one way that can be used to secure data transmission, the data sent will be converted into a certain code and can only be opened by the recipient who has the key to change the code so that the confidentiality of the message or information can be maintained. continue to be supported, and an application is needed to facilitate data processing, a cryptographic web application can be made and used to facilitate data processing.